Écrire collégialement en formation pour soutenir la construction d’une identité collective au sein d’un nouveau corps de professionnel·le·s - Gaëtan Botty; Sandrine Biémar (Éducation et Socialisation)
This contribution examines a training program designed to support the professionalisation of a new professional staff, i.e. the “Délégués au contrat d’objectifs” (D.C.O). In the context of the Wallonia-Brussels Federation of Belgium, engaged in a reform of the governance of its educational system, these intermediary actors provide a link between administration and schools. The reflexive writing carried out individually and collectively in training constitutes the object of the study conducted. Its objective is to gradually participate in the development of a collective professional identity that helps this new staff to act with coherence and unity. The research methodology is based on representational data collected from the D.C.O. who took part in the training. The analyses indicate that meanings given to the writing task as well as the conditions of its implementation influence the process of identity transformation.